C, N, P, K stoichiometric characteristics of the "leaf-root-litter-soil" system in dryland plantations. (October 2022) - Li, Yage; Dong, Xiaoxue; Yao, Wenxiu; Han, Chun; Sun, Shan; Zhao, Changming
Graphical abstract: Highlights: Tree species and afforestation years affected nutrient cycling of plantations. The highest C was in fine roots and the highest N, P and K was in green leaves. Green leaves absorbed more P and maintained P homeostasis to alleviate P limitation. Caragana korshinskii was more suitable for ecological restoration in drylands. Abstract: Plantation's nutrient cycling can regulate and affect the material cycling of ecosystems, which is the key to maintain the sustainable development of the plantation ecosystem. However, the current understanding of the nutrient cycling characteristics of the "leave-root-litter-soil" continuum of dryland plantation ecosystems is limited. Therefore, in the Longzhong Loess Plateau of China, we selected nine typical dryland plantations to carry related research, including two evergreen ( Platycladus orientalis (13-years and 50-years) and Pinus tabuliformis ) and four deciduous ( Caragana korshinskii (13-years, 35-years and 55-years), Armeniaca sibirica, Populus hopeiensis and Tamarix chinensis ) tree species, and measured C, N, P and K contents of green leaves, fine roots, leaf litter and surface soil (0–20 cm). Results showed tree species and afforestation years strongly changed C, N, P and K contents and ratios of green leaves, fine roots, leaf litter and soil components, and also significantly affected leaf N, P and K reabsorption efficiencies. The average N, P and K contents of four components and soil available nitrogen (AN), available phosphorus (AP) and available potassium (AK) contents in deciduous plantations were higher than those in evergreen plantations, resulting in the lower C:N:P:K stoichiometry of deciduous plantations than evergreen plantations. Especially in 55-years C. korshinskii plantation, its soil C, N, AN, AP and AK contents were higher than those in A. sibirica, P. hopeiensis, P. orientalis and P. tabuliformis plantations. Moreover, soil C, N, P, AN, AP and AK contents in C. korshinskii plantations increased significantly with the increase of afforestation years. Thus, C. korshinskii was more suitable for ecological restoration in drylands. Due to the P limitation in plantations, P reabsorption efficiency was higher than N reabsorption efficiency, and significantly negatively correlated with P contents of four components. And green leaves had the homeostasis to soil AP, which may be the nutrient utilization strategies for plantations to alleviate P limitation. Correlation analysis revealed that the C cycling appeared in green leave-fine root and green leave-leaf litter, the N cycling appeared in green leave-leaf litter-soil-fine root, and the P cycling and K cycling appeared in green leave-leaf litter- soil and leaf litter-fine root. These results will provide guidance for ecological restoration and plantation management in drylands.